La innovación en el sector servicios: la contribución de los servicios empresariales intensivos en conocimiento (SEIC) (Innovation in services: The contribution of Knowledge Intensive Business Services (KIBS)) - Romero Amado, Jorge; Lopéz Toache, Vania (Facultad de Contaduría Pública y Administración, 2015)
Abstract: Innovation is vital to the economies and companies that want to compete in an increasingly globalized world. This has been widely studied in the production of goods; however, in the service sector is poorly understood. The Knowledge Intensive Business Services (KIBS) are intermediate companies that provide services to businesses and cover several areas, from legal consulting to human resources, through research and development (R&D), accounting, marketing, etc. This paper presents a review of studies conducted to determine the relevance of KIBS regarding the generation of innovation in production and its role in the national innovation system. Research shows that the influence of KIBS helps to create and disseminate innovation in enterprises and in the regions where they operate, that is why their role is important in the innovation system and in the economy of countries.